Power storage device

The laminate structure in the power storage device, with a greater solvent proportion at the outer periphery, addresses the challenge of maintaining long-term reliability by ensuring the effective area of the negative electrode remains larger than the positive electrode, thus enhancing the device's stability and resistance to external factors.

JP2025049840APending Publication Date: 2025-04-04NITERRA CO LTD

Patent Information

Application Number
JP2023158296
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing power storage devices with electrolytes face challenges in maintaining long-term reliability due to uneven solvent distribution, which affects the effective area of the negative electrode over time.

Method used

A laminate structure is designed with a positive electrode, an electrolyte, and a negative electrode, where the solvent proportion is greater at the outer periphery between the edges of the positive and negative electrodes compared to the central part, ensuring the effective area of the negative electrode remains larger than the positive electrode over time.

Benefits of technology

This configuration enhances the long-term reliability of the power storage device by maintaining the effective area of the negative electrode, reducing the risk of short circuits and improving resistance to external forces and deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025049840000001_ABST
    Figure 2025049840000001_ABST
Patent Text Reader

Abstract

To provide a power storage device capable of improving the long-term reliability thereof.SOLUTION: A power storage device includes a laminate including a positive electrode, an electrolyte and a negative electrode, in order. The electrolyte includes a solvent and a holding body that holds the solvent. The edge of the positive electrode is inside the edge of the negative electrode in plan view, and a rate of the solvent occupying the outer peripheral portion between the edge of the positive electrode and the edge of the negative electrode in the laminate is greater than a rate of the solvent occupying the central part of the laminate in plan view.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electricity storage device including an electrolyte. [Background technology]

[0002] Prior art relating to an electricity storage device including an electrolyte disposed between a positive electrode and a negative electrode, the electrolyte including a solvent and a support for holding the solvent, is disclosed in Patent Document 1. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-89875 Summary of the Invention [Problem to be solved by the invention]

[0004] There is a need to improve the long term reliability of the prior art.

[0005] The present invention has been made in response to this demand, and has an object to provide an electricity storage device capable of improving long-term reliability. [Means for solving the problem]

[0006] A first aspect for achieving this object includes a laminate including, in order, a positive electrode, an electrolyte, and a negative electrode, the electrolyte including a solvent and a support for holding the solvent. In a plan view, the edge of the positive electrode is inside the edge of the negative electrode, and the ratio of the solvent in the outer periphery of the laminate between the edge of the positive electrode and the edge of the negative electrode is greater than the ratio of the solvent in the center of the laminate in a plan view.

[0007] In the second aspect, in the first aspect, the ratio of the solvent in a peripheral portion of the laminate, which is inside the outer periphery in a plan view and overlaps with the edge of the positive electrode, is greater than the ratio of the solvent in a central portion of the laminate.

[0008] In a third aspect, in the first or second aspect, the outer periphery includes a part of the electrolyte.

[0009] In a fourth aspect, in any one of the first to third aspects, the electrolyte includes a solid electrolyte having a garnet-type crystal structure containing Li, La, Zr, and O.

[0010] A fifth aspect is the battery according to any one of the first to fourth aspects, further comprising a separator separating the positive electrode and the negative electrode, the separator containing an electrolyte.

[0011] A sixth aspect is a battery according to any one of the first to fourth aspects, wherein at least one of the positive electrode and the negative electrode includes a current collector, and further includes a separator that separates the positive electrode and the negative electrode, and a protective layer that is in contact with at least one of the separator and the current collector, and the protective layer includes an electrolyte. Effect of the Invention

[0012] According to the present invention, the ratio of the solvent in the outer periphery between the edge of the positive electrode and the edge of the negative electrode of the laminate is greater than the ratio of the solvent in the central part of the laminate, so that the effective area of ​​the negative electrode, which is larger than the positive electrode by the amount of the outer periphery, can be secured for a long period of time, thereby improving the long-term reliability of the electricity storage device. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1(a) is a plan view of the electricity accumulation device according to the first embodiment, and FIG. 1(b) is a cross-sectional view of the electricity accumulation device taken along line Ib-Ib in FIG. 1(a). [Diagram 2] FIG. 2 is an enlarged cross-sectional view of a portion of the laminate. [Diagram 3] FIG. 1 is a diagram illustrating a garnet-type crystal structure. [Figure 4] FIG. 4 is a diagram showing the ratio of a solvent contained in a laminate. [Diagram 5] FIG. 11 is a cross-sectional view of an electricity accumulation device according to a second embodiment. [Figure 6]6(a) is a plan view of an electricity accumulation device according to a third embodiment, and (b) is a cross-sectional view of the electricity accumulation device taken along line VIb-VIb in FIG. 6(a). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. Fig. 1(a) is a plan view of an electricity storage device 10 in a first embodiment. The electricity storage device 10 includes a laminate 11 and flat terminals 12 and 13 (so-called tabs) connected to the laminate 11.

[0015] Fig. 1(b) is a cross-sectional view of the electricity storage device 10 taken along line Ib-Ib in Fig. 1(a). In Fig. 1(b), the thickness of each part is exaggerated (the same applies to Figs. 2, 5, and 6(b)). The laminate 11 includes, in that order, a positive electrode 14, a separator 17, and a negative electrode 20. The laminate 11 is formed by stacking sheet-like positive electrodes 14, separators 17, and negative electrodes 20. The laminate 11 is housed in a case (not shown).

[0016] FIG. 2 is a cross-sectional view of an enlarged portion of the laminate 11. The positive electrode 14 is formed by stacking a current collector 15 and an active material layer 16. The current collector 15 is not particularly limited as long as it has electronic conductivity and can pass current through the active material layer 16. The current collector 15 may be made of a conductive material such as C, Ti, Cr, Ni, Cu, Fe, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Al, Au, or an alloy containing two or more of these conductive materials (e.g., stainless steel). When Fe is used for the current collector 15, it is preferable that it is coated with Ni, Cu, or the like to prevent oxidation. The shape of the current collector 15 is not limited, and examples thereof include a wire, a rod, a plate, a foil, and a porous shape.

[0017] The active material layer 16 contains an electrolyte 23 (described below) and an active material 24. The active material layer 16 may contain a conductive additive to reduce the resistance of the active material layer 16. Examples of the conductive additive include carbon black, acetylene black, ketjen black, carbon fiber, Ni, Pt, and Ag.

[0018] The active material 24 is exemplified by a metal oxide having a transition metal, a sulfur-based active material, and an organic active material. The metal oxide having a transition metal has a carrier ion of Li + For example, LiCoO 2 ,LiNi 0.8 Co 0.15 Al 0.05 O 2 ,LiMn 2 O 4 ,LiNiVO 4 ,LiNi 0.5 Mn 1.5 O 4 ,LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O 4 and LiFePO 4 Examples include:

[0019] Sulfur-based active materials include S and TiS 2 ,NiS,FeS 2 ,Li 2 S,MoS 3 Examples of the organic active material include radical compounds such as 2,2,6,6-tetramethylpiperidinoxyl-4-yl methacrylate and polytetramethylpiperidinoxyl vinyl ether, quinone compounds, radialene compounds, tetracyaquinodimethane, and phenazine oxide.

[0020] The negative electrode 20 is formed by stacking a current collector 21 and an active material layer 22. The current collector 21 is not particularly limited as long as it is a material that has electronic conductivity and can pass current through the active material layer 22. The current collector 21 may be made of, for example, a conductive material such as C, Ti, Cr, Ni, Cu, Fe, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Al, Au, or an alloy containing two or more of these conductive materials (for example, stainless steel). When Fe is used for the current collector 21, it is preferable that it is coated with Ni, Cu, or the like to prevent oxidation. The shape of the current collector 21 is also not limited, and examples thereof include a linear, rod-like, plate-like, foil-like, and porous shape.

[0021] The active material layer 22 includes an electrolyte 23 (described below) and an active material 25. The active material layer 22 may include a conductive additive to reduce the resistance of the active material layer 22. Examples of the conductive additive include carbon black, acetylene black, ketjen black, carbon fiber, Ni, Pt, and Ag.

[0022] Active material 25 is Li + , Na + , K + There is no particular limitation as long as the material is capable of reversibly absorbing and releasing carrier ions such as those mentioned above. The mechanism of ion absorption and release may be dissolution and precipitation of the substance, insertion and desorption of ions between crystal layers, etc. The active material 25 may be, for example, one or more elements selected from the group consisting of Li, Na, K, C, Mg, Al, Si, S, P, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Y, Zr, Nb, Mo, Pd, Ag, Cd, In, Sn, Sb, W, Pb, and Bi, or an alloy, composite, oxide, chalcogenide, or halide using these elements.

[0023] The alloy as the active material 25 is preferably Si-Al, Al-Zn, Si-Mg, Si-La, Al-Ge, Si-Ge, Si-Ag, Si-Sn, Si-Ti, Si-Y, Si-Cr, Si-Ni, Si-Zr, Si-V, Si-Nb, Si-Mo, Zn-Sn, Ge-Ag, Ge-Sn, Ge-Sb, Ag-Sn, Ag-Ge, Sn-Sb, etc., and may be a complete solid solution type alloy, a eutectic alloy, a hypoeutectic alloy, a hypereutectic alloy, or a peritectic type alloy. The oxide is Fe 2 O 3 , CuO, MnO 2 , NiO, Li 4 Ti 5 O 12 , H 2 Ti 12 O 25 , Na 2 Ti 3 O 7etc. may be preferred. The active material 25 may be coated with a material having excellent electronic conductivity or ceramics. Two or more materials may be used for the active material 25. The shape of the active material 25 is not particularly limited, and may be spherical, elliptical, faceted, strip-like, fibrous, scaly, torus-like, or hollow.

[0024] The separator 17 separates the positive electrode 14 from the negative electrode 20. The separator 17 contains an ionically conductive electrolyte 23. The electrolyte 23 contains a solvent and a support that holds the solvent. The support can be, for example, an aggregate of inorganic particles or a polymer.

[0025] When the support is a polymer, the electrolyte 23 is exemplified by a polymer gel electrolyte in which a supporting electrolyte is added to a polymer gel formed by adding a solvent to a polymer (support). Examples of polymer gel electrolytes include homogeneous gels and heterogeneous gels. A homogeneous gel is an electrolyte in which the polymer and the solvent form a homogeneous phase. A heterogeneous gel is an electrolyte in which the crystalline portion of the polymer forms the gel skeleton, and the amorphous portion present between the crystalline network is gelled by the solvent. Examples of polymers include polyethylene oxide, a copolymer of vinylidene fluoride and propylene hexafluoride, polymethyl methacrylic acid, and polyacrylonitrile.

[0026] When the support for the electrolyte 23 is inorganic particles, the inorganic particles are preferably electronically insulating and insoluble in a solvent. The solvent is held in the gaps between the aggregate of inorganic particles, and the entire aggregate holding the solvent becomes the electrolyte 23. Therefore, inorganic particles that exhibit ion conductivity or insulation are used, and a supporting electrolyte is added to the solvent.

[0027] Examples of the solvent include carbonate esters, aliphatic carboxylate esters, phosphate esters, γ-lactones, ethers, nitriles, sulfolane, dimethyl sulfoxide, fluorous solvents, and ionic liquids. Mixtures of these may also be used.

[0028] Examples of carbonate esters include cyclic carbonate esters such as propylene carbonate, ethylene carbonate, butylene carbonate, vinylene carbonate, vinylethylene carbonate, and fluoroethylene carbonate, and chain carbonate esters such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0029] Examples of aliphatic carboxylates include methyl formate, methyl acetate, and ethyl propionate. Examples of phosphates include trimethyl phosphate. Examples of γ-lactones include γ-butyrolactone. Examples of ethers include chain ethers such as 1,3-dioxolane and 1,2-dialkoxyethane, and cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran. Examples of nitriles include acetonitrile and propionitrile. Fluorous solvents are compounds in which the hydrogen atoms of hydrocarbons are replaced with fluorine atoms, and derivatives thereof.

[0030] Ionic liquids are compounds consisting of cations and anions, and are liquid at room temperature and pressure. If the solvent is an ionic liquid, flame retardancy can be improved. The ionic liquid is preferably one having one or more cationic species selected from the group consisting of ammonium, imidazolium, pyrrolidinium, and piperidinium. The anion component of the ionic liquid is not particularly limited. The anion component is preferably BF 4 - ,N(SO 2 F) 2 - Inorganic anions such as B(C 6 H 5 ) 4 - ,CH 3 SO 3 - ,CF 3 SO 3 - ,N(SO 2 CF 3 ) 2 - ,N(SO 2 C 4 F 9 ) 2 - Examples of organic anions include:

[0031] The ionic liquid may be a solvated ionic liquid, for example, a sulfone-based solvent such as sulfolane or a sulfolane derivative, or a glyme-based solvent such as tetraglyme to which a supporting electrolyte has been added.

[0032] Examples of materials for the insulating inorganic particles contained in the electrolyte 23 include oxides such as silica, alumina, ceria, and zirconia, and glasses such as quartz glass and borosilicate glass. Examples of inorganic particles (solid electrolytes) that exhibit ion conductivity include one or more types selected from sulfide-based, hydride-based, halide-based, and oxide-based. Oxide-based solid electrolytes are preferred because they do not generate toxic gases when exposed to the atmosphere.

[0033] In the electrolyte 23, the ratio of the volume of the inorganic particles to the total volume of the inorganic particles and the electrolyte solution is preferably 52% or more and less than 100%, and more preferably 61% or more and less than 100%. Since the interface resistance of the inorganic particles can be reduced by combining the inorganic particles with the electrolyte solution, the transport number of the ions in the electrolyte 23 can be made larger than that of a general electrolyte solution. As a result, the stability of the operation of the electricity storage device 10 in which the electrolyte 23 is disposed is increased.

[0034] The content (volume %) of the inorganic particles and the electrolyte is obtained by freezing the separator 17 or embedding the separator 17 in a tetrafunctional epoxy resin or the like and then analyzing a randomly selected cross section of the separator 17 at a magnification of 5000 times using an SEM equipped with an energy dispersive X-ray spectrometer (EDS). The analysis identifies the distribution of elements and performs image analysis of the contrast of the backscattered electron image to identify the area of ​​the inorganic particles and the area of ​​the electrolyte, and the content (volume %) of the inorganic particles and the electrolyte is obtained by regarding the area ratio in the cross section of the separator 17 as the volume ratio of the electrolyte 23 in the separator 17.

[0035] The carrier ion of electrolyte 23 is Li + For example, sulfide-based solid electrolytes are crystalline thiolithium type, Li 10GeP 2 S 12 type, argyrodite type, Li 7 P 3 S 11 Type, Li 2 SP 2 S 5 Examples of hydride-based solid electrolytes include glass and glass ceramics, such as LiBH 4 and lithium halide compounds (LiI, LiBr, LiCl) and lithium amide (LiNH 2 ) is an example of a solid solution with Li. 3 Y.C.L. 6 Examples are given below.

[0036] Carrier ion is Li + In the case of the above, examples of oxide-based solid electrolytes include NASICON-based materials, LISICON-based materials, oxides having a perovskite structure, oxide glasses, and oxides having a garnet structure. NASICON-based materials are represented by the general formula A x M 2 (TO 4 ) 3 A is a material represented by the formula: A is Na, Li, M is Zr, Ti, V, Mn, Cr, Fe, Ni, Al, Ge, T is P, Si, As, for example, Na 3 V 2 (PO 4 ) 3 , Li 1+x Al x Ti 2-x (PO 4 ) 3 , Li 1+x Ge x Ti 2-x (PO 4 ) 3 LISICON-based materials include Li 4-2x Zinc x GeO 4 (0≦x≦1). Oxides with a perovskite structure include Li x La (1-x) / 3 NbO 3 , La 2 / 3-X Li 3X TiO 3(0≦x≦1).

[0037] Oxide-based glasses are Li 2 O-SiO 2 , Li 2 OP 2 O 5 , Li 2 O-Al 2 O 3 , Li 2 O-Al 2 O 3 -TiO 2 -P 2 O 5 , Li 3-X P(O,N) 4 (LIPON, lithium oxyphosphate). The crystal structure of garnet-type oxides is represented by the general formula C 3 A 2 B 3 O 12 The oxides having a garnet structure are preferred because they have excellent resistance to reduction.

[0038] FIG. 3 is a diagram showing a schematic diagram of a garnet-type crystal structure. In the garnet-type crystal structure, the C-site Sc is dodecahedrally coordinated with the oxygen atom Oa, the A-site Sa is octahedrally coordinated with the oxygen atom Oa, and the B-site Sb is tetrahedrally coordinated with the oxygen atom Oa. In the solid electrolyte, Li may exist in a void V, which is a position where Li is octahedrally coordinated with the oxygen atom Oa in a normal garnet-type crystal structure. The void V is, for example, a position sandwiched between the B-site Sb1 and the B-site Sb2. The Li existing in the void V is octahedrally coordinated with the oxygen atom Oa that constitutes an octahedron including the tetrahedral face Fb1 that forms the B-site Sb1 and the tetrahedral face Fb2 that forms the B-site Sb2. For example, Li having a garnet-type crystal structure may exist in a void V that is a void V that is sandwiched between the B-site Sb1 and the B-site Sb2. 7 La 3 Zr 2 O 12 In the formula, La can occupy the C site Sc, Zr can occupy the A site Sa, and Li can occupy the B site Sb and the void V.

[0039] The garnet-type crystal structure can be identified by X-ray diffraction. The garnet-type crystal structure is found in the Cambridge Structural Database (CSD) X-ray diffraction file No. 422259 (Li 7 La 3 Zr 2 O 12 ) has an XRD pattern similar to that of No. 422259. The solid electrolyte may differ in the type of constituent elements and Li concentration, and therefore the diffraction angle and intensity ratio may differ when compared to No. 422259. The typical crystal structure of this type is a cubic system (space group Ia-3d (- indicates an overline that means a reversal operation), JCPDS: 84-1753).

[0040] Solid electrolytes with a garnet-type crystal structure are typically Li 7 La 3 Zr 2 O 12 Li 7 La 3 Zr 2 O 12 A part of the constituent elements may be replaced with other elements, or a small amount of other elements may be added without replacing the constituent elements. Examples of the other elements include at least one element selected from the group consisting of Mg, Al, Si, Ca, Ti, V, Ga, Sr, Y, Nb, Sn, Sb, Ba, Hf, Ta, W, Bi, Rb, and lanthanoids (excluding La).

[0041] The solid electrolyte is, for example, Li 6 La 3 Zr 1.5 W 0.5 O 12 , Li 6.15 La 3 Zr 1.75 Ta 0.25 Al 0.2 O 12 , Li 6.15 La 3 Zr 1.75 Ta 0.25 Ga 0.2 O 12 , Li 6.25 La 3 Zr 2 Ga0.25 O 12 , Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 , Li 6.5 La 3 Zr 1.75 Te 0.25 O 12 , Li 6.75 La 3 Zr 1.75 Nb 0.25 O 12 , Li 6.9 La 3 Zr 1.675 Ta 0.289 Bi 0.036 O 12 , Li 6.46 Ga 0.23 La 3 Zr 1.85 Y 0.15 O 12 , Li 6.8 La 2.95 Ca 0.05 Zr 1.75 Nb 0.25 O 12 , Li 7.05 La 3.00 Zr 1.95 Gd 0.05 O 12 , Li 6.20 Ba 0.30 La 2.95 Rb 0.05 Zr 2 O 12 Examples include:

[0042] The solid electrolyte preferably contains at least one of Mg and element A (A is at least one element selected from the group consisting of Ca, Sr, and Ba) and the molar ratio of each element satisfies all of the following (1) to (3), or contains both Mg and element A and the molar ratio of each element satisfies all of the following (4) to (6). Element A is preferably Sr in order to increase the ionic conductivity of the solid electrolyte. (1) 1.33≦Li / (La+A)≦3 (2) 0≦Mg / (La+A)≦0.5 (3) 0≦A / (La+A)≦0.67 (4) 2.0≦Li / (La+A)≦2.5 (5) 0.01≦Mg / (La+A)≦0.14 (6) 0.04≦A / (La+A)≦0.17

[0043] Returning to FIG. 2, the active material layers 16, 22 and the separator 17 may contain a binder that binds the inorganic particles together. Examples of the binder include fluorinated resins, polyolefins, polyvinylpyrrolidone, polyvinyl alcohol, cellulose ether, and rubber-like polymers such as styrene butadiene rubber. Examples of the fluorinated resins include vinylidene fluoride polymers, polychlorotrifluoroethylene, polyvinyl fluoride, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, ethylene-tetrafluoroethylene copolymers, and ethylene-chlorotrifluoroethylene copolymers.

[0044] Vinylidene fluoride polymers are -CH 2 CF 2 - is not particularly limited as long as it contains. Examples of vinylidene fluoride polymers include homopolymers of vinylidene fluoride and copolymers of vinylidene fluoride and copolymerizable monomers. Examples of copolymerizable monomers include halogen-containing monomers (excluding vinylidene fluoride) and non-halogen copolymerizable monomers. Examples of halogen-containing monomers include chlorine-containing monomers such as vinyl chloride; fluorine-containing monomers such as trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, and perfluoroalkyl vinyl ether. Examples of non-halogen copolymerizable monomers include olefins such as ethylene and propylene; acrylic monomers such as acrylic acid, methacrylic acid, and esters or salts thereof; and vinyl monomers such as acrylonitrile, vinyl acetate, and styrene. One or more types of copolymerizable monomers are polymerized to vinylidene fluoride to form a copolymer.

[0045] With reference to FIG. 1(b) and FIG. 2, an example of a method for manufacturing an electricity storage device 10 using inorganic particles as a support for the electrolyte 23 will be described. An active material 24 is mixed with a mixture of an electrolyte solution in which a supporting electrolyte is added to a solvent and a support, and a solution in which a binder is dissolved in a solvent is further mixed to make a slurry. After tape casting on a current collector 15 such as aluminum foil, the mixture is dried to obtain a green sheet including an active material layer 16. Next, an electrolyte solution in which a supporting electrolyte is added to a solvent and a support are mixed, and a solution in which a binder is dissolved in a solvent is further mixed to make a slurry for the separator 17. After tape casting on the active material layer 16, the mixture is dried to obtain a positive electrode sheet including a first layer 18.

[0046] An active material 25 is mixed with a mixture of an electrolyte solution in which a supporting electrolyte has been added to a solvent and a support, and a solution in which a binder has been dissolved in a solvent is further mixed to produce a slurry. After tape casting on a current collector 21 such as copper foil, the mixture is dried to obtain a green sheet including an active material layer 22. Next, a slurry for the separator 17 is applied onto the active material layer 22, and then dried to obtain a negative electrode sheet including a second layer 19.

[0047] The positive electrode sheet and the negative electrode sheet are cut so that the size of the positive electrode sheet is smaller than the size of the negative electrode sheet, and then the positive electrode sheet is overlaid on the negative electrode sheet so that the first layer 18 of the positive electrode sheet is in contact with the second layer 19 of the negative electrode sheet, thereby obtaining a laminate 11.

[0048] The distance between the rolls of a roll press machine (not shown) is set to, for example, about 60% of the thickness of the laminate 11 before roll pressing, and the laminate 11 is passed between the rolls, and a force is applied to the laminate 11 in a direction pressing the current collectors 15, 21 against each other. This results in the laminate 11 having the separator 17 made by overlapping the first layer 18 and the second layer 19. The flat terminal 12 is joined to the current collector 15 of the positive electrode 14, and the flat terminal 13 is joined to the current collector 21 of the negative electrode 20, and then the resultant is sealed in a case (not shown) to obtain the electricity storage device 10.

[0049] In a plan view, an edge 26 of the positive electrode 14 (see FIG. 1(a)) is inside an edge 27 of the negative electrode 20, so that an outer periphery 28 is formed between the edge 26 of the positive electrode 14 and the edge 27 of the negative electrode 20. The outer periphery 28 is provided outside the edge 26 around the entire periphery of the edge 26 of the positive electrode 14. A portion of the flat terminal 12 overlaps the outer periphery 28.

[0050] The outer periphery 28 includes a part of the separator 17 and a part of the negative electrode 20. Since the part of the laminate 11 where the positive electrode 14 overlaps is thicker than the outer periphery 28, the force with which the part where the positive electrode 14 overlaps is pressed by the roll is greater than the force with which the outer periphery 28 is pressed by the roll. As a result, when the laminate 11 passes between the rolls, the solid content contained in the part where the positive electrode 14 overlaps is pressed, the volume of the gap or gel is reduced, and some of the solvent present in the gap or gel is pushed out and moves to the outer periphery 28. When the pressure of the rolls is reduced, the amount of solvent that moves to the outer periphery 28 is reduced, and when the pressure of the rolls is increased, the separator 17, the negative electrode 20, etc. may be destroyed. Therefore, the pressure (distance between the rolls) is set so that a sufficient amount of solvent moves to the outer periphery 28 without destroying the separator 17, the negative electrode 20, etc.

[0051] Fig. 4 is a diagram showing the ratio of the solvent contained in the laminate 11. Fig. 4 is a schematic diagram in which the horizontal axis indicates the position of each part between the outer peripheral part 28 of the laminate 11 and the central part 30 of the laminate 11 in a plan view, and the vertical axis indicates the ratio of the solvent contained in each part of the laminate 11. The ratio of the solvent contained in the laminate 11 is determined by thermogravimetric differential thermal analysis (TG-DTA) of a sample obtained by cutting out a part of the laminate 11 over the entire thickness direction of the laminate 11. The position of the central part 30 of the laminate 11 coincides with the geometric center when the positive electrode 14 is viewed in a plan view.

[0052] When taking a sample for TG-DTA from the outer periphery 28, the laminate 11 is cut out over the entire thickness direction, whereas when taking a sample for TG-DTA from the central portion 30, the laminate 11 is cut out over the entire thickness direction after the positive electrode 14 is peeled off from the laminate 11. Since the positive electrode 14 is not present in the outer periphery 28, the sample from the central portion 30 is also cut out of the positive electrode 14 in the same way as the sample from the outer periphery 28, in order to equalize the conditions for the TG-DTA subject.

[0053] Since the negative electrode 20 (see FIG. 1(b)) is larger than the positive electrode 14 by the amount of the outer periphery 28, it is possible to reduce electrodeposition that occurs when ions that have migrated from the positive electrode 14 to the negative electrode 20 have nowhere to go during charging of the electricity storage device 10. Since the proportion of the solvent in the outer periphery 28 is larger than the proportion of the solvent in the central portion 30 of the laminate 11, the effective area of ​​the negative electrode 20, which is larger than the positive electrode 14 by the amount of the outer periphery 28, can be secured for a long period of time.

[0054] For example, in outer periphery 28, the corners (corners of second layer 19) of separator 17 (see FIG. 1(b)) are exposed, and when an external force is applied to laminate 11, there is a risk that the corners of separator 17 may be damaged and that the damage to separator 17 may result in damage to active material layer 22. However, the solvent present in large amounts in outer periphery 28 increases the adhesion of outer periphery 28, and the strength of the corners of separator 17 and the edges of active material layer 22 increases, so that damage to separator 17 and negative electrode 20 can be reduced. This makes it possible to improve the long-term reliability of electricity storage device 10 against external forces.

[0055] The solvent present in a large amount in the outer periphery 28 ensures ion diffusibility in the outer periphery 28 of the negative electrode 20, thereby reducing electrodeposition occurring in the negative electrode 20. Since short circuits between the positive electrode 14 and the negative electrode 20 caused by electrodeposition can be reduced, the long-term reliability of the electricity storage device 10 against electrodeposition can be improved.

[0056] Since the solvent increases the adhesiveness of the outer periphery 28, a part of the flat terminal 12 overlaps the outer periphery 28, thereby reducing the turning over of the flat terminal 12 by the outer periphery 28. Since peeling of the current collector 15 due to deformation of the flat terminal 12 can be reduced, the long-term reliability of the electricity storage device 10 against deformation of the flat terminal 12 can be improved.

[0057] The ratio of the solvent in the peripheral portion 29 of the laminate 11, which is inside the outer periphery 28 in a plan view and overlaps with the edge 26 of the positive electrode 14, is greater than the ratio of the solvent in the central portion 30, so that the diffusibility of ions in the peripheral portion 29 of the negative electrode 20 can be ensured. Since the electrodeposition occurring in the negative electrode 20 can be further reduced, defects due to short circuits between the positive electrode 14 and the negative electrode 20 caused by electrodeposition can be reduced.

[0058] An electricity storage device 40 in the second embodiment will be described with reference to Fig. 5. In the first embodiment, the separator 17 contains the electrolyte 23. In the second embodiment, the protective layers 44, 47 contain the electrolyte 23. The same parts as those described in the first embodiment are given the same reference numerals, and the following description will be omitted. Fig. 5 is a cross-sectional view of the electricity storage device 40 in the second embodiment. In the second embodiment, a liquid-based lithium ion battery in which a supporting electrolyte is added to a solvent is exemplified as the electricity storage device 40.

[0059] The electricity storage device 40 (laminate) includes, in this order, a positive electrode 41, a separator 43, and a negative electrode 45. These are housed in a case (not shown). The separator 43 is made of a porous material that is durable against the active material 24 of the positive electrode 41, the negative electrode 45, and the electrolyte, and allows carrier ions to pass through but has no electronic conductivity. Examples of the separator 43 include nonwoven fabrics and porous membranes made of cellulose, polypropylene, polyethylene, etc.

[0060] The positive electrode 41 is formed by overlapping a current collector 15 and an active material layer 42. The active material layer 42 contains an active material 24. In order to reduce the resistance of the active material layer 42, the active material layer 42 may contain a conductive assistant such as carbon black, acetylene black, ketjen black, carbon fiber, Ni, Pt, or Ag.

[0061] A protective layer 44 is disposed between the separator 43 and the negative electrode 45. The protective layer 44 contains the electrolyte 23.

[0062] The negative electrode 45 is formed by stacking an active material layer 46, a protective layer 47, and a current collector 21 in that order. The active material layer 46 is made of, for example, Li, a Li-Al alloy, a Li-Sn alloy, a Li-Si alloy, a Li-Mg alloy, a Li-Si alloy, or a Si-Li alloy. The protective layer 47 contains an electrolyte 23. The protective layers 44 and 47 are arranged by sheet lamination, coating on the separator 43 or the current collector 21, or the like.

[0063] The oxide-based solid electrolyte having a garnet-type crystal structure containing Li, La, Zr, and O in the protective layers 44, 47 is resistant to reduction by the metallic lithium of the active material layer 46, and therefore, when the solid electrolyte is contained in the protective layers 44, 47, the operation stability of the electricity storage device 40 is increased. The protective layer 44 interposed between the active material layer 46 and the separator 43 suppresses short circuits caused by dendritic growth of metallic lithium. The protective layer 47 interposed between the active material layer 46 and the current collector 21 suppresses deterioration of the current collector 21.

[0064] An electricity storage device 50 in the third embodiment will be described with reference to Fig. 6. In the first and second embodiments, electricity storage devices 10, 40 were described in which positive electrodes 14, 41, separators 17, 43, and negative electrodes 20, 45 were arranged between a pair of current collectors 15, 21. In the third embodiment, an electricity storage device 50 including a bipolar electrode in which a positive electrode 52 and a negative electrode 53 are provided on both sides of a current collector 51 will be described. The same parts as those described in the first embodiment are denoted by the same reference numerals, and the following description will be omitted.

[0065] Fig. 6(a) is a plan view of an electricity storage device 50 according to a third embodiment. Fig. 6(b) is a cross-sectional view of the electricity storage device 50 taken along line VIb-VIb in Fig. 6(a).

[0066] 6(b), in an electricity storage device 50 (laminate), a separator 17 is disposed between bipolar electrodes in which active material layers 16, 22 are disposed on both sides of a current collector 51. The overlapping portion of the current collector 51 and the active material layer 16 constitutes a positive electrode 52, and the overlapping portion of the current collector 51 and the active material layer 22 constitutes a negative electrode 53. The negative electrode 53 is larger than the positive electrode 52.

[0067] As shown in FIG. 6(a), an outer periphery 56 is formed between an edge 54 of the positive electrode 52 and an edge 55 of the negative electrode 53 (see FIG. 6(b)). The outer periphery 56 is provided outside the edge 54 around the entire periphery of the positive electrode 52. The proportion of the solvent in the outer periphery 56 is greater than the proportion of the solvent in a central portion 57 of the laminate 50. This allows the electricity storage device 50 to achieve the same effects as the electricity storage device 10 in the first embodiment.

[0068] The present invention has been described above based on an embodiment, but the present invention is not limited to the above embodiment, and it can be easily inferred that various improvements and modifications are possible within the scope of the present invention without departing from the spirit of the present invention.

[0069] In the embodiment, the positive electrodes 14, 52 and the negative electrodes 20, 53 are rectangular in plan view, but this is not necessarily limited to this. The positive electrodes 14, 52 and the negative electrodes 20, 53 may be any shape, such as a circle or an ellipse.

[0070] In the embodiment, the active material layers 16, 22 and the separator 17 all contain the electrolyte 23, but this is not necessarily limited to this. In the electricity storage devices 10, 50, it is sufficient that at least the separator 17 contains the electrolyte 23.

[0071] In the second embodiment, a case has been described in which the protective layer 44 exists between the active material layer 46 and the separator 43, and the protective layer 47 exists between the current collector 21 and the active material layer 46, but this is not necessarily limited to this. It is of course possible to omit one of the protective layers 44, 47. It is also of course possible to dispose at least one of the protective layers 44, 47 in the electricity storage device 10 in the first embodiment. [Explanation of symbols]

[0072] 10. Energy storage devices 11 Laminate 14 Positive electrode 17 Separator 20 negative electrode 21 Current collector 23 Electrolytes 26 Positive electrode edge 27 Negative electrode edge 28 Outer periphery 29 Periphery 30 Central part 40 Electricity storage device (laminate) 41 Positive electrode 43 Separator 44,47 Protective layer 45 Negative electrode 50 Electricity storage device (laminate) 52 Positive electrode 53 Negative electrode 54 Positive edge 55 Negative electrode edge 56 Outer periphery 57 Central part

Claims

1. a laminate including, in order, a positive electrode, an electrolyte, and a negative electrode; The electrolyte includes a solvent and a support that holds the solvent, An electricity storage device, in which an edge of the positive electrode is inside an edge of the negative electrode in a plan view, An electricity storage device, in which a proportion of the solvent in an outer peripheral portion of the laminate between an edge of the positive electrode and an edge of the negative electrode is greater than a proportion of the solvent in a central portion of the laminate in a planar view.

2. The electricity storage device according to claim 1 , wherein a ratio of the solvent in a peripheral portion of the laminate that is inside the outer periphery in a plan view and overlaps with the edge of the positive electrode is greater than a ratio of the solvent in the central portion.

3. The electricity storage device according to claim 1 , wherein the outer circumferential portion includes a part of the electrolyte.

4. 3. The electricity storage device according to claim 1, wherein the electrolyte contains a solid electrolyte containing Li, La, Zr and O and having a garnet-type crystal structure.

5. A separator is provided to separate the positive electrode and the negative electrode, The electricity storage device according to claim 1 , wherein the separator contains the electrolyte.

6. At least one of the positive electrode and the negative electrode includes a current collector; a separator separating the positive electrode and the negative electrode; a protective layer in contact with at least one of the separator and the current collector, The electricity storage device according to claim 1 , wherein the protective layer contains the electrolyte.

Citation Information

Patent Citations

  • Nonaqueous electrolyte solution, semisolid electrolyte layer, sheet for secondary battery and secondary battery

    JP2021089875A

Cited By

  • Method of processing substrate, method of manufacturing semiconductor device, program, and substrate processing apparatus

    EP4814160A1

  • Multi-half pipe heat exchange system for electric arc, metallurgical or refining furnaces and system thereof

    US12435926B2